A nationwide survey of hypoplastic myelodysplastic syndrome (a multicenter retrospective study). Issue 12 (28th September 2017) - Kobayashi, Takashi; Nannya, Yasuhito; Ichikawa, Motoshi; Oritani, Kenji; Kanakura, Yuzuru; Tomita, Akihiro; Kiyoi, Hitoshi; Kobune, Masayoshi; Kato, Junji; Kawabata, Hiroshi; Shindo, Motohiro; Torimoto, Yoshihiro; et al.
Abstract: Hypoplastic myelodysplastic syndrome (hMDS) is a distinct entity with bone marrow (BM) hypocellularity and the risk of death from BM failure (BMF). To elucidate the characteristics of hMDS, the data of 129 patients diagnosed between April 2003 and March 2012 were collected from 20 institutions and the central review team of the National Research Group on Idiopathic Bone Marrow Failure Syndromes, and compared with 115 non‐hMDS patients. More RA and fewer CMMoL and RAEB‐t in French‐American‐British (FAB) and more RCUD and MDS‐U and fewer RCMD in World Health Organization (WHO) classifications were found in hMDS than non‐hMDS with significant differences. The overall survival (OS) and AML progression‐free survival (AML‐PFS) of hMDS were higher than those of non‐hMDS, especially in patients at age ≥50 and of lower risk in Revised International Prognostic Scoring System (IPSS‐R). In competing risks analysis, hMDS exhibited decreased risk of AML‐progression in lower IPSS or IPSS‐R risk patients, and higher risk of death from BMF in patients at age ≥50. Poor performance status (PS ≥2) and high karyotype risks in IPSS‐R (high and very high) were significant risk factors of death and AML‐progression in Cox proportional hazards analysis.